DFT Study of Nickel‐Catalyzed Low‐Temperature Methanol Synthesis. Issue 10 (6th April 2017) - McGuinness, David S.; Patel, Jim; Amin, Mohamad Hassan; Bhargava, Suresh K.
Abstract: Low‐temperature methanol synthesis (CO+2 H2 →CH3 OH) catalyzed by a homogeneous nickel/alkali metal alkoxide system has been studied theoretically. Two broad mechanistic possibilities, the direct hydrogenation of CO by nickel formyl species and indirect hydrogenation via methyl formate formation, have been examined. The most favorable mechanism involves the methanolysis of CO to methyl formate catalyzed by an ether complex of sodium methoxide followed by the stepwise hydrogenation of methyl formate to formaldehyde and then to a nickel methoxide, in which both steps are mediated by a nickel hydride. In the final step the nickel methoxide is hydrogenated to release methanol. The conversion of methyl formate to the nickel methoxide is predicted to be rate limiting, and the nickel hydride is the most likely catalyst resting state. The theoretical results are discussed in the context of existing experimental observations, and a good agreement with past studies was obtained. Abstract : Direct or Indirect? The mechanism of CO hydrogenation to methanol catalyzed by the Ni/alkali alkoxide system is studied by DFT. Direct hydrogenation of CO by nickel formyl species and indirect hydrogenation via methyl formate formation, have been examined. The theoretical results are discussed in the context of existing experimental observations, and a good agreement with past studies was obtained.